Study on the Mechanism of Liquid Carbon Dioxide Fracturing and Permeability Enhancement Technology in Low Permeability Thick Coal Seam. (14th October 2022) - Yu, Rui; Wang, Xinfeng; Wang, Zhaofeng; Wang, Long; Zhang, Xiaoqiang; Liu, Wengang; Zhang, Qiao
Abstract : For the urgent need of gas management in high gas and coal and gas herniated mines, liquid CO2 fracturing is used to increase the permeability and promote the pumping treatment of low permeability coal seams. In this paper, we construct the coal deformation and damage model, gas diffusion and seepage model, and coal seam permeability change model; simulate and solve the plastic zone and gas pressure of coal seam after fracturing with the COMSOL Multiphysics software; and set 4 different hole spacing groups of 2 m, 3 m, 4 m, and 5 m and 3 different hole layout methods of single hole, double hole, and net hole to get the best solution for liquid CO2 fracturing. At the same time, the specific effect of liquid CO2 on coal seam fracturing was verified by field experiments using coal seam No. 2 of the 12316 comprehensive mining working face of Wangjialing Coal Mine as the background of the study. The numerical simulation results show that the stress concentration area around the fracturing hole appears in single-hole fracturing, and the coal seam is prone to fatigue damage in this area, but the damage range is limited, and the reduction of gas pressure after fracturing is small; the fracturing effect of double-hole and net-hole fracturing is better than that of single-hole fracturing due to the existence of sufficient critical air surface. After negative pressure extraction, the coal seam gas pressure is positively correlated with the distance from extraction hole to fracturing hole, and the best extraction effect can be seen from the field experimental results with the netted hole layout at the hole distance of 3 m. The field test results show that the pure amount of gas extraction is improved about 4 times after liquid CO2 fracturing, which proves that liquid CO2 fracturing has a better enhancement effect on gas management in low permeability coal seams.